Prevalence of uterine infections in the post partum period of dystocia affected buffaloes and its effect on fertility - JADON, R S; DHALIWAL, G S; JAND, S K (The Indian Journal of Animal Reproduction, 2005)
The objective of the study was to find the prevalence of different types of bacterial infections, especially anaerobes in the uterine lumen and its impact on subsequent fertility. Out of 19 dystocia affected buffaloes studied during days 24-60 postpartum, 11 (58%) had uterine infections with 8 (42%) animals having mixed infection of Arcarwbacter pyogenes and gram negative obligate anaerobes such as Fusobacterium spp. and Bacteroides spp. and voided whitish thick pus and none conceived subsequently. While the other three were infected with aerobes only (2 infected with Pseudomonas auregi,wsa and l with A. pyogenes); they came into estrus and conceived by day 109 postpartum. The uterus of remaining eight animals was sterile and all conceived by day 89 postpartum. These observations suggest that a pathogenic synergism exists between A. pyogenes and gram-negative obligate anaerobes, which might have increased severity of uterine infections, and consequently affected conception.